2020
DOI: 10.1530/ec-20-0411
|View full text |Cite
|
Sign up to set email alerts
|

DUOX2 variants are a frequent cause of congenital primary hypothyroidism in Thai patients

Abstract: Objective: To identify genetic etiologies of congenital primary hypothyroidism (CH) in Thai patients. Design and methods: CH patients were enrolled. Clinical characteristics including age, signs and symptoms of CH, pedigree, family history, screened thyroid-stimulating hormone results, thyroid function tests, thyroid imaging, clinical course and treatment of CH were collected. Clinical exome sequencing by next-generation sequencing was performed. In-house gene list which covered 62 potential candidate genes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…However, patients with normal-sized GIS accounted for the majority of the cases in our cohort. Meanwhile, the frequency of genetic defects in the genes causing DH was higher than that in the genes causing TD, which was in agreement with previous studies in China and other Asian countries (11)(12)(13). These studies suggested that DH might be the leading pathophysiology of CH in Chinese populations, in contrast to what has been reported in other populations.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, patients with normal-sized GIS accounted for the majority of the cases in our cohort. Meanwhile, the frequency of genetic defects in the genes causing DH was higher than that in the genes causing TD, which was in agreement with previous studies in China and other Asian countries (11)(12)(13). These studies suggested that DH might be the leading pathophysiology of CH in Chinese populations, in contrast to what has been reported in other populations.…”
Section: Discussionsupporting
confidence: 90%
“…The higher frequency of variants in DUOX2 was consistent with the observation of a higher proportion of DH cases in our participants. Variants in DUOX2 have been frequently reported, especially in East Asia (11)(12)(13)(14). Several studies have suggested that the most reported variants among Chinese, Japanese, and Thai patients with CH have been identified in DUOX2 (12,13,15), suggesting that DUOX2 variants are an even more frequent causative factor for CH than previously recognized.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…p.Pro138Leu, p.Pro142Arg and p.Leu264Cysfs*57 are located in the peroxidase-like domain, whereas p.Gln899Serfs*21, p.Thr920Ile and p.Phe966Serfs*29 are present in the transmembrane domain. Only two variants were described previously associated with congenital hypothyroidism, the p.Pro138Leu [46, 47] and the p.Phe966Serfs*29 variant [6, 11,24,40,41,46,[48][49][50][51]. The frameshift p.Phe966Serfs*29, commonly reported as p.S965fsX994 is one of the most frequent mutations in DUOX2 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral blood samples of the patients were prospectively collected. Genomic DNA was extracted in a manner similar to that described previously [17]. To identify the variants, clinical exome sequencing was performed using the Illumina MiSeq V R system (Illumina, San Diego, CA) with the TruSight One Sequencing Panel V R .…”
Section: Dna Sequencing and Data Analysismentioning
confidence: 99%